Oral Dosed Organo-Silica Nanoparticles Restore Glucose Homeostasis and β-Cell Function in Diabetes Rats - Chu, Chenxiao; Wei, Mingli; Bian, Che; Bi, Xiaoshuang; Deng, Yaxin; Xiao, Peifu; Zhao, Jiansong; Wang, Yuying; He, Haibing; Gou, Jingxin; Yin, Tian; Tang, Xing; et al. (Wiley-VCH, 2026)
Type 2 diabetes mellitus (T2DM) persists as a global health challenge, with current therapies inadequately addressing the intertwined pathologies of hyperglycemia, oxidative stress, and β-cell dysfunction. Here, an oral nanotherapeutic platform, MOP@T@D, engineered to restore glucose homeostasis and rejuvenate pancreatic β-cells is developed. The platform is constructed by co-loading insulin and glucose oxidase (GOx) into diselenide-bridged mesoporous organosilicon nanoparticles (MON), followed by sequential coating with transferrin (Tf) and functionalization with deoxycholic acid (Dc). MOP@T@D demonstrates efficient intestinal absorption and liver-targeted delivery, achieving an oral bioavailability of 10.6%. Under hyperglycemic conditions, GOx-generated H2O2 cleaves the diselenide bonds in the MON framework, resulting in rapid insulin release with 8.7-fold higher cumulative release compared to normoglycemic conditions. Simultaneously, the metabolized selenium derivatives progressively upregulate key selenoproteins, enhancing glutathione peroxidase (Gpx) activity by 31%, which effectively neutralizes oxidative stress and suppresses NF-κB-mediated inflammation. In a T2DM rat model, this therapy increases the islet area by 26.7% and restores insulin secretion to 74.6% of the physiological level. Notably, the system maintains normal blood glucose levels for two weeks after cessation of administration. In summary, through a simple oral dose, MOP@T@D not only stabilizes glycemic fluctuations but also addresses the root pathophysiology of T2DM.